2014
DOI: 10.1039/c4ra03172e
|View full text |Cite
|
Sign up to set email alerts
|

Successful aqueous processing of a lead free 0.5Ba(Zr0.2Ti0.8)O3–0.5(Ba0.7Ca0.3)TiO3 piezoelectric material composition

Abstract: We report on the successful aqueous processing of a lead free piezoelectric 0.5Ba(Zr 0 2 Ti 0 8 )O 3 0.5(Ba 0 7 Ca 0 3 )TiO 3 (BZT BCT) composition with the final functional properties of the materials unaffected by the various processing steps involved. X-ray diffraction results show a single tetragonal perovskite crystalline phase for the as-received sintered BZT BCT powder. The purity of the perovskite phase for BZT BCT powder was found to be controlled even after ageing the material in water for 24 h as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…However, the application of BT-based materials is limited by their low Curie temperature (T C ) and single functional performance [4]. To address these issues, many researchers have attempted modification of BT-based materials by doping/substituting elements, broadening their performance capabilities by endowing the materials with optical, electrical, acoustic, or/and magnetic properties [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…However, the application of BT-based materials is limited by their low Curie temperature (T C ) and single functional performance [4]. To address these issues, many researchers have attempted modification of BT-based materials by doping/substituting elements, broadening their performance capabilities by endowing the materials with optical, electrical, acoustic, or/and magnetic properties [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Such potential gains derived from processing could be a way to exclude sintering additives from Zr 1Àx Sn x TiO 4 compositions. Our recent ndings 15,17,18 stimulated us to achieve the successful aqueous colloidal processing of Zr 1Àx Sn x TiO 4 composition and further prepare high quality spherical granules by freeze granulation (FG), resulting in ceramics with high green dense compact on consolidation. FG can help ceramic manufacturers achieve powder formulations with superior homogeneity, pressing performance and dispersibility.…”
Section: 3mentioning
confidence: 99%
“…An increase in packing efficiency and compact density will enhance the densication ability upon sintering while implying a decrease in total shrinkage. 15,18 This is conrmed by the data plotted in Fig. 6 that compares the dilatometry curves of all types of powder compacts (FG-ZST, NG-ZST and NG-ZST-ZnO) monitored within the temperature range from room temperature (RT) to 1400 C. The FG-ZST curve exhibits a negative inclination along the lower temperature range probably because of the homogeneous distribution of binder among the particles, and its burnout enables the particles to gradually approach each other.…”
Section: C2 Structural Properties Of Sintered Zst Ceramicsmentioning
confidence: 99%
“…The earlier findings [25][26][27][28][29][30] prepared from dry milled BT and AM BT powders and ultrasonicated for minutes to de-agglomerate the BT particles, followed by particle size distribution measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Several research works on aqueous processing of BT have reported suspensions with solid loadings up to 40 vol.% with dispersion of powders being achieved via pH variations or by adding dispersing agents. 29,30 Such processing difficulties were successfully overcome through a suitable thermochemical surface treatment given to the powder particles to prevent hydrolysis, improve their dispersion ability in water, increase the solid loadings and enhance colloidal stability, without damaging final properties of the sintered material.…”
Section: Introductionmentioning
confidence: 99%